An Autopsy Based Study on Patterns of Injury in Homicidal Deaths in Imphal - Das , N G; Singh , T B (Journal of Indian Academy of Forensic Medicine, 2023)
The pattern of homicide may be a useful indicator of the social stresses in a community and may also provide useful information for law enforcement strategies and thus pattern of injury in such cases could possibly give a better understanding the manner of death. This is a prospective descriptive analysis of medico-legal autopsies performed in the mortuary of Regional Institute of Medical Sciences, Imphal from October 2013 to August 2015. In this study a total of 97 cases of homicide during the study period is analysed in various medico-legal aspects. Blunt weapon, firearm and bomb blast were commonest weapon employed. Multiple injuries and head injuries were commonest cause of death. This study is taken up to analyze the pattern of injuries in all homicidal deaths and to formulate measures for improvement of scenario etc.